Detection Thresholds of Archaeological Features in Airborne Lidar Data from Central Yucatán. Issue 3 (August 2016) - Magnoni, Aline; Stanton, Travis W.; Barth, Nicolas; Fernandez-Diaz, Juan Carlos; León, José Francisco Osorio; Ruíz, Francisco Pérez; Wheeler, Jessica A.
Abstract: In this article we evaluate ∼48km 2 of airborne lidar data collected at a target density of 15 laser shots/m in central Yucatán, Mexico. This area covers parts of the sites of Chichén Itzá and Yaxuná, a kilometer-wide transect between these two sites, and a transect along the first few kilometers of Sacbé 1 from Yaxuná to Cobá. The results of our ground validation and mapping demonstrate that not all sizable archaeological features can be detected in the lidar images due to: (1) the slightly rolling topography interspersed with 1-6 m-high bedrock hummocks, which morphologically mimic house mounds, further complicated by the presence of low foundations; (2) the complex forest structure in central Yucatán, which has particularly dense near-ground understory resulting in a high number of mixed-signal ground and low vegetation returns which reduces the fidelity and accuracy of the bare-earth digital elevation models; and (3) the predominance of low archaeological features difficult to discern from the textural noise of the near-ground vegetation. In this article we explore different visualization techniques to increase the identification of cultural features, but we conclude that, in this portion of the Maya region, lidar should be used as a complement to traditional on-the-ground survey techniques.